Paul and Caristanius at Pisidian Antioch - Mowery, Robert L. (Biblica, 2006)
A recently-published Latin inscription from Pisidian Antioch refers to four benefactions that a prominent citizen named Caristanius had provided to fulfill a vow on behalf of the emperor Claudius. Since this inscription refers to the year 45/46 CE, it refers to benefactions that may have been provided near the time when Paul arrived in the city. After surveying the contents of this inscription and reviewing scholarly opinion concerning the date when Paul arrived, this paper reflects on the ethnic diversity of first century Pisidian Antioch, the religious beliefs reflected in Caristanius’ vow, the likely impact of his benefactions on the residents of the city, and the possibility that he may have been one of “the leading men of the city” mentioned in Acts 13,50.